New Zealand Memorial (eastern handle), Anzac Parade, Canberra, 2002 - McDonald, Damian, 1971- (2002)
The New Zealand Memorial consists of a bronze representation of the handles of a flax basket. The design is based on a Maori proverb 'You at that handle, and I at this handle of the basket'. Image shows the eastern handle at the southern end of Anzac Parade.
Condition: Good.
Part of collection: Collection of photographs of Anzac Parade, Canberra, 2002.
Also available online
Keywords: New Zealand Memorial (Canberra, A.C.T.) -- Photographs; Monuments -- Australian Capital Territory -- Canberra -- Photographs; War memorials -- Australian Capital Territory -- Canberra -- Photographs; Anzac Parade (Canberra, A.C.T.) -- Photographs; Canberra (A.C.T.) -- Buildings, structures, etc. -- Photographs